A Quasi‐Multinary Composite Coating on a Nickel‐Rich NCM Cathode Material for All‐Solid‐State Batteries. Issue 6 (21st March 2022) - Kitsche, David; Strauss, Florian; Tang, Yushu; Bartnick, Nikolai; Kim, A‐Young; Ma, Yuan; Kübel, Christian; Janek, Jürgen; Brezesinski, Torsten
Abstract: Inorganic solid‐state batteries are attracting significant interest as a contender to conventional liquid electrolyte‐based lithium‐ion batteries but still suffer from several limitations. The search for advanced coatings for protecting cathode materials in solid‐state batteries to achieve interfacial stability is a continuing challenge. In the present work, the surface of an industrially relevant Ni‐rich LiNi x Co y Mn z O2 cathode material, NCM‐851005 (85 % Ni), was modified by applying a coating containing Li, Nb and Zn, aiming at a composition Li6 ZnNb4 O14, by means of sol‐gel chemistry. Detailed characterization using scanning transmission electron microscopy combined with energy‐dispersive X‐ray spectroscopy and nano‐beam electron diffraction showed that the surface layer after heating in O2 at 500 °C contains Li3 NbO4 nanocrystals and Li2 CO3, with Zn presumably acting as a dopant. The protective coating on the NCM‐851005 secondary particles significantly increased the cycling performance (reversible capacity, rate capability etc.) and stability of full cells using argyrodite Li6 PS5 Cl as solid electrolyte. Interestingly, the level of improvement is superior to that achieved with conventional LiNbO3 coatings. Abstract : Rocksalt coating : Lithium thiophosphate‐based solid‐state battery cells using a layered Ni‐rich NCM cathode active material show excellent cycling performance after coating of the secondary particles with a protective Li−Nb−O‐type nanocomposite layer.